Random mutagenesis-based screening of the interface of phyllogen, a bacterial phyllody-inducing effector, for interaction with plant MADS-box proteins - Kitazawa, Yugo; Iwabuchi, Nozomu; Maejima, Kensaku; Matsumoto, Oki; Suzuki, Masato; Matsuyama, Juri; Koinuma, Hiroaki; Oshima, Kenro; Namba, Shigetou; Yamaji, Yasuyuki (Frontiers in Plant Science, 2023)
To understand protein function deeply, it is important to identify how it interacts physically with its target. Phyllogen is a phyllody-inducing effector that interacts with the K domain of plant MADS-box transcription factors (MTFs), which is followed by proteasome-mediated degradation of the MTF. Although several amino acid residues of phyllogen have been identified as being responsible for the interaction, the exact interface of the interaction has not been elucidated. In this study, we comprehensively explored interface residues based on random mutagenesis using error-prone PCR. Two novel residues, at which mutations enhanced the affinity of phyllogen to MTF, were identified. These residues, and all other known interaction-involved residues, are clustered together within the protein structure of phyllogen, indicating that they constitute the interface of the interaction. Moreover, in silico structural prediction of the protein complex using ColabFold suggested that phyllogen interacts with the K domain of MTF via the putative interface. Our study facilitates an understanding of the interaction mechanisms between phyllogen and MTF.